Pengaruh Promosi, Harga Dan Kepercayaan Terhadap Kepuasan Konsumen Pada Toko Isna Collection Di Raman Utara - Yateno, Yateno; Fuadi, Selamet; Wardani, Yunita Setiyo (Jurnal Manajemen DIVERSIFIKASI, 2023)
Consumer satisfaction is an effort to maintain customers. For this reason, entrepreneurs mustfurther improve the performance and quality of their products so that consumers feel satisfiedand become customers for a long time. The formulation of the problem in this study is "Doespromotion, price and trust have a joint effect on consumer satisfaction". From theseproblems, the purpose of this study is to determine and analyze the effect of promotion, priceand trust together on consumer satisfaction. This research method is quantitative. Thetechnique used in collecting research data uses library research techniques, field research,documentation, interviews and questionnaires. Then in data analysis using quantitativemethods, the data is collected and then analyzed. analysis using multiple linear regressionanalysis and processed using SPSS. Based on the SPSS data analysis, it can be concluded thatpromotion, price and trust have a positive and significant effect on consumer satisfaction atthe Isna Collection Store in North Raman.